MANAGEMENT MODEL TO MEASURE AND EVALUATE PHYSICIANS DUAL PRACTICE (DP) - Muruga, Kirathimo (European Journal of Business and Strategic Management, 2022)
Purpose: The aim of this study was to develop a Management model that can measure and evaluate physicians Dual Practice in the Kenyan health sector. Methodology: The paper adopted a desk top research design. The design involves a review of existing studies relating to the research topic. Desk top research is usually considered as a low cost technique compared to other research designs (Beal et al., 2012). In this case, the researcher collected information relating to physicians Dual Practice. Results: Based on past literature, the study concluded that several factors are vital in influencing physicians having Dual Practice. These factors included; infrastructure, working environment, doctor's promotion and income level. The cost/value of DP was also highlighted as an important determinant. Further, the study concluded that legal framework has a significant moderating influence on physicians having Dual Practice. In addition, the study concluded that the level of physicians' satisfaction determined their tendency to engage in Dual Practice. Unique Contribution to Theory, Practice and Policy: Based on the findings, the study recommended the need for stakeholders in the health sector to understand the concept of Dual Practice. In particular, there is need to understand the causes and implications of Dual Practice. The study also recommended the need to develop a management model that can measure and evaluate physicians Dual Practice. It is not advisable to completely ban Dual Practice since it has some positive impact. At the same time, excessive Dual Practice can be counterproductive and could be a threat to the efficiency, quality and equity of health services, especially in the public sector. Hence, the need to develop a management approach and management model that can ensure improved cost-benefit of physicians having Dual Practice.